Management of fibrolamellar hepatocellular carcinoma - Chaudhari, Vikram A.; Khobragade, Krunal; Bhandare, Manish; Shrikhande, Shailesh V. (Chinese Clinical Oncology; Vol 7, No 5 (October 31, 2018): Chinese Clinical Oncology (Recent Advances in Primary Liver Cancers), 2018)
Fibrolamellar hepatocellular carcinoma (FLHCC) is a primary liver tumor. It is a pathologically distinct variety of hepatocellular carcinoma (HCC). The term ‘fibrolamellar’ is derived from the presence of thick fibrous collagen bands surrounding the tumor cells. It is a relatively rare tumor of unknown biology. It has a distinctive predilection for adolescents and young adults with no underlying liver disease or cirrhosis. FLHCC patients have higher incidence of lymph node involvement than conventional HCC patients probably owing to larger median tumor size at presentation. Most cases present at an advanced stage at the time of initial diagnosis, however, curative intent treatment options can still be offered to up to 70% of patients. Surgery (resection/liver transplantation) is the current mainstay of treatment and remains the only potentially curative option. As recurrences are common, alternative therapies are under investigation. FLHCCs have traditionally been considered less chemo-responsive than their conventional HCC counterparts, but in advanced cases multimodality treatments can be effective. Compared to stage-matched non-cirrhotic patients with HCC, patients with FLHCC do not have a favourable prognosis and do not respond differently to treatment. The survival advantage observed in FLHCC over conventional HCC is most likely due to younger age at presentation and absence of cirrhosis.